Toward a nitrogen footprint calculator for Tanzania - Hutton, M.O.; Leach, A.; Leip, A.; Galloway, J.N.; Bekunda, Mateete A.; Sullivan, C.; Lesschen, Jan Peter (2017)
We present the first nitrogen footprint model for a developing country: Tanzania. Nitrogen (N) is a crucial element for agriculture and human nutrition, but in excess it can cause serious environmental damage. The Sub-Saharan African nation of Tanzania faces a two-sided nitrogen problem: while there is not enough soil nitrogen to produce adequate food, excess nitrogen that escapes into the environment causes a cascade of ecological and human health problems. To identify, quantify, and contribute to solving these problems, this paper presents a nitrogen footprint tool for Tanzania. This nitrogen footprint tool is a concept originally designed for the United States of America (USA) and other developed countries. It uses personal resource consumption data to calculate a per-capita nitrogen footprint. The Tanzania N footprint tool is a version adapted to reflect the low-input, integrated agricultural system of Tanzania. This is reflected by calculating two sets of virtual N factors to describe N losses during food production: one for fertilized farms and one for unfertilized farms. Soil mining factors are also calculated for the first time to address the amount of N removed from the soil to produce food. The average per-capita nitrogen footprint of Tanzania is 10 kg N yr−1. 88% of this footprint is due to food consumption and production, while only 12% of the footprint is due to energy use. Although 91% of farms in Tanzania are unfertilized, the large contribution of fertilized farms to N losses causes unfertilized farms to make up just 83% of the food production N footprint. In a developing country like Tanzania, the main audiences for the N footprint tool are community leaders, planners, and developers who can impact decision-making and use the calculator to plan positive changes for nitrogen sustainability in the developing world.